Implications of parents' knowledge, attitude and practices of child physical abuse in building a safer world (2017)
This study investigated parents' knowledge, attitude and practices of child physical abuse in Ogun State. The descriptive survey research design was adopted. A convenience sample of202 male and female parents from Abeokuta South and Odeda Local Government Area of Ogun state were selected using stratified and random sampling technique. A self-developed questionnaire tagged “Parents' Knowledge, Attitudes and Practices of Child Physical abuse Scale” was used for data collection. Simple percentages and means were used in answering the research questions. It was found that parents' knowledge of what constitute child physical abuse and practice is low. Though, most parents condemned child physical abuse there were believes that some abusive acts can be used as disciplinary measures. It was recommended that enlightenment programmes should be organized and intensified to create more awareness and fast track a paradigm shift from the use of abusive punitive strategies by parents and caregivers to build a safer world